2010
DOI: 10.1029/2009jd013322
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric influence on the seasonal cycle of nitrous oxide in the troposphere as deduced from aircraft observations and model simulations

Abstract: [1] The atmospheric N 2 O variations between the Earth's surface and the lower stratosphere, simulated by an atmospheric general circulation model-based chemistry transport model (ACTM), are compared with aircraft and satellite observations. We validate the newly developed ACTM simulations of N 2 O for loss rate and transport in the stratosphere using satellite observations from the Aura Microwave Limb Sounder (Aura-MLS), with optimized surface fluxes for reproducing N 2 O trends observed at the surface statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 68 publications
7
71
0
Order By: Relevance
“…(3) The N 2 O concentration data lower by more than 2.7 ppb (3s at altitudes 4Á6 km over eastern Japan) than the long-term trends were defined as STEinfluenced samples (open circles in Figure A1 in Supplementary file). In general, the STE events are frequent above 7 km over Japan (Ishijima et al, 2010). It is noted that the N 2 O criterion in this study is less restrictive than that of 1.0 ppb in Assonov et al (2013), who also applied a similar method for analysing data taken by passenger aircraft.…”
Section: Data Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…(3) The N 2 O concentration data lower by more than 2.7 ppb (3s at altitudes 4Á6 km over eastern Japan) than the long-term trends were defined as STEinfluenced samples (open circles in Figure A1 in Supplementary file). In general, the STE events are frequent above 7 km over Japan (Ishijima et al, 2010). It is noted that the N 2 O criterion in this study is less restrictive than that of 1.0 ppb in Assonov et al (2013), who also applied a similar method for analysing data taken by passenger aircraft.…”
Section: Data Analysesmentioning
confidence: 99%
“…Previous studies have reported details of the Tohoku University (TU) aircraft observations for CO 2 (Tanaka et al, 1987;Nakazawa et al, 1993b), N 2 O (Ishijima et al, 2001(Ishijima et al, , 2010 and O 2 /N 2 (Ishidoya et al, 2012). To collect air samples using aircraft, two programs have been conducted (Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the factors controlling the stratospheric distributions of N 2 O isotopocules, a numerical simulation was conducted using the Center for Climate System Research/National Institute for Environmental Studies/Frontier Research Center for Global Change atmospheric general circulation model with chemical reactions (CCSR/NIES/FRCGC ACTM) (Ishijima et al, 2010(Ishijima et al, , 2015. Because Ishijima et al (2015) have already given a detailed description of the N 2 O isotopocule model, we briefly explain it here.…”
Section: Simulation Using a Three-dimensional Chemical Transport Modelmentioning
confidence: 99%